1980
DOI: 10.1111/j.1365-3180.1980.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth and response to atrazine between and within susceptible and resistant biotypes of Chenopodium album L.

Abstract: Summary: Differential growth and response to atrazine were examined in greenhouse experiment with three populations of Chenopodium album from southwestern Ontario: two known susceptible (SI. SII) and one resistant (R). Germination of the resistant biotype was less than SII but the same as SI. R seedlings were not as mature at 16 days and weighed less at 23 days than seedlings of SI and SII. Within SI. early‐(ESI) and late‐flowering (LSI) variants were recognized. Older plants of R (37 and 44 days) had a greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
3

Year Published

1981
1981
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 12 publications
6
32
0
3
Order By: Relevance
“…This is in contrast to annual broadleaf weeds that developed resistance to the s-triazine herbicides. With few exceptions, there was a cost to the development of resistance to these herbicides (Anderson et al 1996;Conrad and Radosevich 1979;Marriage and Warwick 1980;Warwick and Black 1981;Elliot and Peirson 1983;Holt 1988). Variability in fitness between susceptible and resistant biotypes does not occur to the same extent with other herbicide groups (AlcocerRuthling et al 1992;O'Donovan et al 1994b;Thompson et al 1994;Gill et al 1996;Wiederholt and Stoltenberg 1996a,b).…”
Section: Growth and Competitivenessmentioning
confidence: 99%
“…This is in contrast to annual broadleaf weeds that developed resistance to the s-triazine herbicides. With few exceptions, there was a cost to the development of resistance to these herbicides (Anderson et al 1996;Conrad and Radosevich 1979;Marriage and Warwick 1980;Warwick and Black 1981;Elliot and Peirson 1983;Holt 1988). Variability in fitness between susceptible and resistant biotypes does not occur to the same extent with other herbicide groups (AlcocerRuthling et al 1992;O'Donovan et al 1994b;Thompson et al 1994;Gill et al 1996;Wiederholt and Stoltenberg 1996a,b).…”
Section: Growth and Competitivenessmentioning
confidence: 99%
“…Warwick and Black (1981) found that susceptible plants of C. album had greater above-ground and reproductive biomass production than the résistant plants. But Marriage and Warwick (1980) biotype and two susceptible ones. Susceptible biotypes of redroot pigweed {Amaranthus retroflexusL.)…”
Section: Non-competitive Experimentsmentioning
confidence: 99%
“…With time, the susceptible biotype accumulâtes more dry matter to develop a dense canopy over the less productive résistant biotype. Marriage and Warwick (1980) hâve reported that s-triazine résistant seedlings of C. album had a slower growth rate than the susceptible seedlings up to 23 d after émergence. Thus the susceptible biotype starts with a marked compétitive advantage over the résistant one during the initial stage of growth.…”
Section: Modes Of Compétition Experimentsmentioning
confidence: 99%
See 2 more Smart Citations